Mitochondrial Supercomplexes: Physiological Organization and Dysregulation in Age-Related Neurodegenerative Disorders - Novack, Gisela V.; Galeano, Pablo; Castaño, Eduardo M.; Morelli, Laura (Frontiers in Endocrinology, 2020)
Several studies suggest that the assembly of mitochondrial respiratory complexes into structures known as supercomplexes (SCs) may increase the efficiency of the electron transport chain, reducing the rate of production of reactive oxygen species. Therefore, the study of the (dis)assembly of SCs may be relevant for the understanding of mitochondrial dysfunction reported in brain aging and major neurodegenerative disorders such as Alzheimer’s disease (AD) and Parkinson’s disease (PD). Here we briefly reviewed the biogenesis and structural properties of SCs, the impact of mtDNA mutations and mitochondrial dynamics on SCs assembly, the role of lipids on stabilization of SCs and the methodological limitations for the study of SCs. More specifically, we summarized what is known about mitochondrial dysfunction and SCs organization and activity in aging, AD and PD. We focused on the critical variables to take into account when postmortem tissues are used to study the (dis)assembly of SCs. Since few works have been performed to study SCs in AD and PD, the impact of SCs dysfunction on the alteration of brain energetics in these diseases remains poorly understood. The convergence of future progress in the study of SCs structure at high resolution and the refinement of animal models of AD and PD, as well as the use of iPSC-based and somatic cell-derived neurons, will be critical in understanding the biological relevance of the structural remodeling of SCs